2015
DOI: 10.1038/cddis.2015.225
|View full text |Cite
|
Sign up to set email alerts
|

Autoregulatory loop between TGF-β1/miR-411-5p/SPRY4 and MAPK pathway in rhabdomyosarcoma modulates proliferation and differentiation

Abstract: The origin of rhabdomyosarcoma (RMS) remains controversial. However, specific microRNAs (miRNAs) are downregulated in RMS and it is possible that re-expression of these miRNAs may lead to differentiation. Transforming growth factor-β1 (TGF-β1) is known to block differentiation of RMS. We therefore analyzed miRNA microarrays of RMS cell lines with or without TGF-β1 knockdown and identified a novel anti-oncogene miR-411-5p. Re-expression of miR-411-5p inhibited RMS cell proliferation in vitro and tumorigenicity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
34
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 48 publications
1
34
0
1
Order By: Relevance
“…zhao et al (26) found that miR-411 overexpression increased cell proliferation in lung cancer by regulating cell cycle regulators. However, Sun et al (35) found that miR-411 served as a tumour suppressor miRNA in rhabdomyosarcoma by inhibiting cell growth both in vitro and in vivo. Guo et al revealed that resumed expression of miR-411 repressed cell growth and metastasis in breast cancer (27,28).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…zhao et al (26) found that miR-411 overexpression increased cell proliferation in lung cancer by regulating cell cycle regulators. However, Sun et al (35) found that miR-411 served as a tumour suppressor miRNA in rhabdomyosarcoma by inhibiting cell growth both in vitro and in vivo. Guo et al revealed that resumed expression of miR-411 repressed cell growth and metastasis in breast cancer (27,28).…”
Section: Discussionmentioning
confidence: 99%
“…Several direct targets of miR-411 have been validated. These targets include IL-18 (36) in malignant pleural mesothelioma, ITCH (25) in hepatocellular carcinoma, SPRY4 in rhabdomyosarcoma (35), FOXO1 (26) in lung cancer, SP1 (27) and GRB2 (28) in breast cancer. In the present study, bioinformatic analysis predicted that PIK3R3 is a potential target of miR-411.…”
Section: Discussionmentioning
confidence: 99%
“…Transforming growth factor-β1 (TGF-β1) is considered key contributor to the progression of breast cancer [ 3 , 4 ]; TGF-β1 signaling features a growth inhibitory effect at an early stage of breast cancer cells, but aggressive oncogenic activity at the advanced malignant state [ 5 7 ]. Recent results indicate an association between TGF-β1 signaling and microRNAs (miRNAs, miR), as revealed by our previous studies in rhabdomyosarcoma [ 8 , 9 ] and those of others about breast cancers [ 4 , 10 13 ], providing new insight into the nature of cancer.…”
Section: Introductionmentioning
confidence: 69%
“…MiRNAs, which are noncoding RNAs that regulate target gene expression post-transcriptionally, show unbalanced expression in cancers [ 14 ], and there is increasing evidence of the efficacy of miRNA-based therapies [ 15 ]. Considering that TGF-β1 promotes the progression of breast cancer at advanced stages [ 3 , 4 ], we assumed that miRNA expression inhibited by TGF-β1 must have antitumor potential, as previously demonstrated for miR-450b-5p [ 8 ] and miR-411-5p [ 9 ]. Using TGF-β1 knockdown colorectal cancer cells (HT-29, SW620 and LoVo) and comprehensive locked nucleic acid microarray analyses, five significantly raised miRNAs were selected (Tracking Number: GSE53338, unpublished data), and their expression was examined in breast cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, a tumor suppressor role has been recognized in several of the downregulated miRNAs from the 14q32 region through the targeting of key oncogenes in glioblastoma, neuroblastoma, metastatic lung cancer, hepatic cancer, pituitary adenoma and rhabdomyosarcoma [3034]. For example, restoration of miR-370 expression led to downregulation of FOXM1 in acute myeloid leukemia, promoting cell growth arrest and senescence [35].…”
Section: Discussionmentioning
confidence: 99%